Effects of 4A Zeolite Additions on the Structure and Performance of LDPE Blend Microfiltration Membrane through Thermally Induced Phase Separation Method - Gu, Jin; Lai, Aonan; Zhang, Jun; Bai, Yunxiang; Zhang, Chunfang; Sun, Yuping (Journal of Membrane and Separation Technology, 2012)
Microfiltration membranes, 4A zeolite/LDPE, were prepared by blending low density polyethylene (LDPE) and 4A zeolite through thermally induced phase separation (TIPS) process with diphenyl ether (DPE) as diluent. The effects of 4A zeolite loading on the pore structure and water permeation performance of the 4A zeolite/LDPE blend membranes were investigated. The incorporation of 4A zeolite particles greatly enhanced the connectivity of membrane pores, the pore size, and thus the water flux of 4A zeolite/LDPE blend membranes due to the gradually stronger DPE-zeolite affinity with the increase of the 4A zeolite loading. The water flux increased from 0 of LDPE control membrane to 87 L/m2h of 4A zeolite/LDPE blend membrane with 4A zeolite loading of 10 wt%. In addition, increasing the DPE content and cooling bath temperature is in favor of the water flux of 4A zeolite/LDPE blend membranes.